MODEL OF PERCEIVED INFLUENCE OF ACADEMIC PERFORMANCE USING SOCIAL NETWORKING - David, Oye Nathaniel; Helou, Adam Mahamat; Ab.Rahim, Nor Zairah (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Social networking sites have created a new social dimension where individuals can increase their social awareness by keeping in touch with old friends, making new friends, getting new data or products and gathering information in other aspects of everyday life. This helps individuals become more knowledgeable, which is very beneficial for students. Based on this, the paper proposed a model of perceived influence of academic performance using social networking. The proposed model was interpreted based on the academic performance of FSKSM (Faculty of computer Science and Information systems) students using SNSs in UTM. The study confirmed that majority of students agreed the social networking media have positive influence on their academic performance. Hence there is need for FSKSM policy makers to evolve strategies to guide and ensure that social networking sites are adopted mostly for academic purposes especially among the undergraduate students of the faculty.